Empirical Analysis of Paddy Value Chains in Nepal: Evidence from Logistic Regression Modeling - Sah, Deepa Kumari; Devkota, Niranjan (Quest Journal of Management and Social Sciences, 2024)
Background: In the South Asian region, rice is one of the most significant staple food crops. The value chain provides a lot of support for a seamless operation from growth to reaching clients' hands. It not only aids farmers, but it also creates opportunities at every stage. As a result, the goal of this research is to determine the value chain analysis of paddy products in Nepal. Objective: The objectives of the study were to analyse value chain analysis of paddy product, and to identify the constraints and opportunities of rice value chain in Parsa, Siraha and Saptari districts of Nepal. Method: The thesis followed the design of explanatory research and collected data using structured questionnaires. Binary logistic Model was used for inferential analysis. Siraha, Saptari and Birgunj (Parsa) districts are chosen purposely. 260 respondents were conveniently sampled from farmers and traders. Result: The study shows the cooperatives play role in accessing credit, accessing inputs, and training with the help of government and non-government organization. The study tells us the fact that paddy value chain functions in a traditional way, there is no innovative way of integrating the chain actors. The cooperatives are involved in both input supply and credit service. Ages, off-farm income, access to information, access to input are the factors that add value in paddy value chain. Conclusion: This research is based on value chain analysis of paddy product in Parsa, Siraha and Saptari districts. Generally, the price of rice/paddy goes down in the post-harvest period due to heavy arrivals in the market and later shoots up, which results in unstable price. Providing better access to credit to farmers to reduce dependence on money lenders can solve the existing problem. Paper Types: Research Paper Keywords: Value Chain Analysis, Framers, Traders, Value addition, Logistic Model, Kobo toolbox. JEL Classification: N55, C8, Q18, Q24, Q25